MOTIVASI TOKOH OGINO GINKO UNTUK MERAIH GELAR DOKTER DALAM NOVEL HANAUZUMI KARYA JUN’ICHI WATANABE - I Putu, Agnes Andika (Humanis, 2015)
The title of this research is “Motivation of Ogino Ginko to reach a doctor degree in Hanauzumi’s novel by Jun’ichi Watanabe”. The problems of study are 1) how the motivation of Ogino Ginko to reach a doctor degree and 2) how the effort done to reach a doctor degree. The theories used in this research are the literaturepsychologyand the theory of motivation by Petry (in Risnawita and Ghufron, 1981). The methodsused collecting are used library method and note technique. The methodsused in data analysis are qualitative method technique. Presentation of data analysis used informal method. The results of this research show the motivations of Ogino Ginko to reach a doctor degree are divide into two, namely intrinsic motivation and extrinsic motivation. The intrinsic motivation are the pudency and Ogino Ginko’s solidarity against women. The extrinsic motivation are the encouragementfrom herfriend and rewards. the effort done by Ogino Ginko to reach a doctor degree are getting permits from her mother, take formal educations, and attempted to pass of the medical license exam.
Keywords: literature psychology, intrinsic motivation, extrinsic motivation